Prevalence and incidence of psychotic disorders in 22q11.2 deletion syndrome: a meta-analysis. (17th November 2022) - Provenzani, Umberto; Damiani, Stefano; Bersano, Ilaria; Singh, Simran; Moschillo, Antonella; Accinni, Tommaso; Brondino, Natascia; Oliver, Dominic; Fusar-Poli, Paolo
Abstract: 22q11.2 deletion syndrome (22q.11.2DS) might be one of the strongest genetic risk factors for psychosis, but robust estimates of prevalence and incidence of psychotic disorders in this condition are not available. To address this gap, we performed a multistep systematic PRISMA/MOOSE-compliant literature search of articles reporting prevalence (primary outcome) or incidence (secondary outcome) of psychotic disorders in 22q11.2DS samples (protocol: https://osf.io/w6hpg ) using random-effects meta-analysis, subgroup analyses and meta-regressions. The pooled prevalence of psychotic disorders was 11.50% (95%CI:9.40–14.00%), largely schizophrenia (9.70%, 95%CI:6.50–14.20). Prevalence was significantly higher in samples with a mean age over 18 years, with both psychiatric and non-psychiatric comorbidities and recruited from healthcare services (compared to the community). Mean age was also significantly positively associated with prevalence in meta-regressions ( p < 0.01). The pooled incidence of psychotic disorders was 10.60% (95%CI:6.60%-16.70%) at a mean follow-up time of 59.27 ± 40.55 months; meta-regressions were not significant. To our knowledge, this is the first comprehensive systematic review and meta-analysis of the prevalence and incidence of psychotic disorders in 22q11.2DS individuals. It demonstrates that around one in ten individuals with 22q11.2DS displays comorbid psychotic disorders, and around one in ten will develop psychosis in the following five years, indicating that preventive approaches should be implemented systematically in 22q11.2DS.